Dynamic arterial elastance as a predictor of arterial pressure response to norepinephrine weaning in mechanically ventilated patients with vasoplegic syndrome—a systematic review and meta-analysis - Zhou, Xiaoyang; Hu, Caibao; Pan, Jianneng; Xu, Chang; Xu, Zhaojun; Pan, Tao; Chen, Bixin (Frontiers in Cardiovascular Medicine, 2024)
Introduction: During the de-escalation phase of circulatory shock, norepinephrine weaning may induce diverse arterial pressure responses in patients with different vasomotor tones. Dynamic arterial elastance (Eadyn) has been extensively studied to predict the arterial pressure response to interventions. We conducted this meta-analysis to systematically assess the predictive performance of Eadyn for the mean arterial pressure (MAP) response to norepinephrine weaning in mechanically ventilated patients with vasoplegic syndrome. Materials and methods: A systematic literature search was conducted on May 29, 2023 (updated on January 21, 2024), to identify relevant studies from electronic databases. The area under the hierarchical summary receiver operating characteristic curve (AUHSROC) was estimated as the primary measure of diagnostic accuracy because of the varied thresholds reported. Additionally, we observed the distribution of the cutoff values of Eadyn, while computing the optimal value and its corresponding 95% confidential interval (CI). Results: A total of 5 prospective studies met eligibility, comprising 183 participants, of whom 67 (37%) were MAP responders. Eadyn possessed an excellent ability to predict the MAP response to norepinephrine weaning in patients with vasoplegic syndrome, with an AUHSROC of 0.93 (95% CI: 0.91 to 0.95), a pooled sensitivity of 0.94 (95% CI: 0.85 to 0.98), a pooled specificity of 0.73 (95% CI: 0.65 to 0.81), and a pooled diagnostic odds ratio of 32.4 (95% CI: 11.7 to 89.9). The cutoff values of Eadyn presented a nearly conically symmetrical distribution; the mean and median cutoff values were 0.89 (95% CI: 0.80 to 0.98) and 0.90 (95% CI: not estimable), respectively. Conclusions: This meta-analysis with limited evidences demonstrates that Eadyn may be a reliable predictor of the MAP response to norepinephrine weaning in mechanically ventilated patients with vasoplegic syndrome.